A spatial and temporal assessment of Maleo (Macrocephalon maleo) nesting behavior and habitat preferences through integrated field and modeling approaches - Rosalia, Nurma; Hamidun, Marini Susanti; Dunggio, Iswan; Baderan, Dewi Wahyuni K.; Zakaria, Zuliyanto (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The Maleo (Macrocephalon maleo) is a Sulawesi-endemic bird with high conservation concern due to habitat degradation and population decline. The Panua Nature Reserve is a key Maleo habitat in Gorontalo Province, yet lacks updated data on habitat use and distribution patterns. This study aims to analyze Maleo presence in nesting grounds, evaluate habitat utilization, predict its distribution, and provide conservation recommendations. Methods: The research used direct surveys via camera traps and spatial modeling using the Maximum Entropy (MaxEnt) algorithm. Data were collected over five months, and analysis included the Relative Abundance Index (RAI) and occupancy modeling to assess habitat suitability and species detection. Finding: Maleo nesting pairs increased by 68.52% from 2022 to 2023. The species exhibited bimodal daily activity (peaks at 06:00–09:00 and 16:00–18:00), with habitat preference for geothermal zones and coastal forests. The RAI was 9.33%, and occupancy rate was estimated at 55%. MaxEnt modeling revealed 7,544.78 ha of highly suitable habitat, concentrated in grids N10, J13, K14, and M09, with an AUC of 0.826, indicating high predictive accuracy. Conclusion: Maleo birds in Panua Nature Reserve are showing a positive nesting trend. However, habitat fragmentation and human activities continue to threaten their sustainability. Strategic management is needed to maintain habitat integrity and support species conservation. Novelty/Originality of this article: This study integrates field-based camera trap data with predictive spatial modeling to provide a comprehensive habitat suitability analysis for the endangered Maleo in Panua Nature Reserve—an approach not yet applied in this location. The findings offer actionable conservation insights and prioritize critical zones for protection.